2005
DOI: 10.1038/nm1177
|View full text |Cite|
|
Sign up to set email alerts
|

Experimental autoimmune encephalomyelitis repressed by microglial paralysis

Abstract: Although microglial activation occurs in inflammatory, degenerative and neoplastic central nervous system (CNS) disorders, its role in pathogenesis is unclear. We studied this question by generating CD11b-HSVTK transgenic mice, which express herpes simplex thymidine kinase in macrophages and microglia. Ganciclovir treatment of organotypic brain slice cultures derived from CD11b-HSVTK mice abolished microglial release of nitrite, proinflammatory cytokines and chemokines. Systemic ganciclovir administration to C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
544
2
4

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 681 publications
(571 citation statements)
references
References 46 publications
21
544
2
4
Order By: Relevance
“…A similar beneficial effect of microglia in stroke was reported in a study where there was a 60 % increase in infarct size by selective elimination of microglia, which the effect was reversed by repopulating the cells [65]. In contrast, microglia ablation was either protective or had no effect in models of other neurodegenerative diseases, including Alzheimer's disease [66], amyotrophic lateral sclerosis [67], and experimental autoimmune encephalomyelitis [68].…”
Section: Microgliasupporting
confidence: 64%
“…A similar beneficial effect of microglia in stroke was reported in a study where there was a 60 % increase in infarct size by selective elimination of microglia, which the effect was reversed by repopulating the cells [65]. In contrast, microglia ablation was either protective or had no effect in models of other neurodegenerative diseases, including Alzheimer's disease [66], amyotrophic lateral sclerosis [67], and experimental autoimmune encephalomyelitis [68].…”
Section: Microgliasupporting
confidence: 64%
“…We, therefore, used GCV treatment of CD11b-HSVtk transgenic cultures for effective ablation of microglial contribution. Microglia from transgenic CD11b-HSVtk mice become paralyzed or die in the presence of GCV (Heppner et al, 2005). LPS has been shown to contain impurities capable of signaling through other TLRs.…”
Section: Discussionmentioning
confidence: 99%
“…Using transgenic mice carrying the selective ablation of proliferating microglia and undergoing experimental MS, it has been recently shown that the inhibition of microglia cells prevents the development and maintenance of the inflammatory CNS lesions [94]. Finally, a direct association between the intensity of microglia activation and EAE symptom gravity has been reported [2].…”
Section: The Eae Animal Modelmentioning
confidence: 99%